Pengaruh Suhu dan Waktu Penggorengan Terhadap Kualitas Keripik Pisang Saas Lumajang - I Ketut Mahardika; Singgih Baktiarso; Ummi Zahrotul Ainiyah; Najihah Meilani Putri; Ervinatus Tiri Wulansari; Ummi Qonitatin (Peneliti.net, 2023)
This research discusses the relationship between temperature optimization and frying time to improve the quality of banana chips. The purpose of this study was to determine the relationship between temperature optimization and frying time to improve the quality of banana chips, especially the agung banana type in the SAAS chips business and to obtain the best temperature and frying time in the production process. This study used a free variable, namely the temperature to be used, which ranged from 70°C, 80°C and 90°C as well as the time variation, which ranged from 30 minutes, 40 minutes and 50 minutes. So that from these variations the best banana chips can be produced based on direct testing of the panelists. The choice of temperature ranges from 70 ºC to 90 ºC with the aim of avoiding excessive changes in taste and color. During the frying process using cooking oil as much as 12 liters. This research partners with one of the banana chip businesses in Lumajang, namely SAAS Lumajang banana chips, where their business uses a type of agung banana.